Potentiometric determination of stability constants of cobalt (II) with some substituted 1,2,4-triazoline-3-thione derivatives - (:unkn) unknown (My University, 1996)
In the present study, the protonation and stability constants of cobalt (II) complexes of some substituted 1,2,4-triazoline-3-thione derivatives were investigated. These compounds have previously been synthesised and their activities reported. The mole fractions of different species derived from ligand and complex were determined in relation to their pH values.
Keywords: 1,2,4-triazoline-3-thione; cobalt (II) complexes; stability constants